HISTOMORPHOLOGY OF PANCREATIC TISSUE IN MEDAKA FISH (Oryzias javanicus): STUDY OF DIABETIC ANIMAL MODEL DEVELOPMENT - Akmal, Muhammad Ichlasul; Laila, Sri Rahmatul; Wresdiyati, Tutik (Jurnal Kedokteran Hewan, 2023)
This study aimed to explore the histomorphology of the pancreatic tissue of medaka fish to develop medaka fish as a diabetic animal model. Adult medaka fish were obtained with a body length of 2.530.22 cm and a weight of 265.825 g. Medaka fish were fixed using Boiun's fixative solution. Macro anatomical observations of the pancreas were conducted using a stereomicroscope. Histological preparations were made according to the Hematoxylin-eosin staining standard procedure. Pancreatic histomorphology of medaka fish was carried out using a light microscope with 100x and 400x magnification. The macro anatomy observations of the pancreas showed the interconnection with several tissues, such as spleen, gallbladder, liver, fat, and intestines. The pancreas was located toward the liver, oversees the intestines, and covered with fat. Pancreatic histomorphological observations showed exocrine cells composed of serous pyramidal acinar cells and endocrine cells (islets of Langerhans). Intralobular and intercalated ducts (ducts of Boll) were composed of simple cuboidal epithelium. This study concluded that the pancreas organ in medaka fish is a single organ, and histomorphologically has both of exocrine and endocrine cells.